Luthers oversættelse af Zakarias’ Bog - Jensen, Christian Højgaard (Dansk Teologisk Tidsskrift, 2016)
Luther’s Deutsche Bibel (1545) is a manifestation of Luther’s understanding of the Holy Scriptures as being intrinsically clear, in contrast to the four-fold hermeneutics that influenced both scholastics and spiritualists. This article analyzes Luther’s translation and exposition of the book of Zechariah. Three themes – salvation history, Christology and aesthetics – are argued to be fundamental to Luther’s understanding of Old Testament scripture and, hence, to his translation of Zechariah. These three themes are seen as concretizations of Luther’s all-encompassing assumption of Christ as the eternal Logos who pervades all of Scripture, an assumption that refuses to treat the text as a symbol. On the contrary, the meaning of the text is inherently bound to the grammar of the text, and this understanding explains Luther’s emphasis on the salvation history described in the Old Testament.